Therapeutic Potential of Microvesicles in Cell Therapy and Regenerative Medicine of Ocular Diseases With an Especial Focus on Mesenchymal Stem Cells-Derived Microvesicles - Rad, Lina Moallemi; Yumashev, Alexey V.; Hussen, Bashdar Mahmud; Jamad, Hazha Hadayat; Ghafouri-Fard, Soudeh; Taheri, Mohammad; Rostami, Samaneh; Niazi, Vahid; Hajiesmaeili, Mohammadreza (Frontiers in Genetics, 2022)
These days, mesenchymal stem cells (MSCs), because of immunomodulatory and pro-angiogenic abilities, are known as inevitable factors in regenerative medicine and cell therapy in different diseases such as ocular disorder. Moreover, researchers have indicated that exosome possess an essential potential in the therapeutic application of ocular disease. MSC-derived exosome (MSC-DE) have been identified as efficient as MSCs for treatment of eye injuries due to their small size and rapid diffusion all over the eye. MSC-DEs easily transfer their ingredients such as miRNAs, proteins, and cytokines to the inner layer in the eye and increase the reconstruction of the injured area. Furthermore, MSC-DEs deliver their immunomodulatory cargos in inflamed sites and inhibit immune cell migration, resulting in improvement of autoimmune uveitis. Interestingly, therapeutic effects were shown only in animal models that received MSC-DE and were not seen in animals treated with fibroblasts-derived exosomes (FIB-DE). In this review, we summarized the therapeutic potential of MSCs and MSC-DE in cell therapy and regenerative medicine of ocular diseases.